PENGGUNAAN KARTU AKSARA JAWA NGLEGENO BERBASIS EDUGAME DALAM PEMBELAJARAN BAHASA JAWA DI MADRASAH IBTIDAIYAH: - Tarsim (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
ABSTRACT: The purpose of this study is the use of the Ngggeno Javanese script in learning Javanese in Madrasah Ibtidaiyah. How to collect data using observation, interviews, tests, and documents. Data analysis technique used is an interactive analysis technique that consists of three components, namely data reduction, data presentation, and drawing conclusions. The conclusion of this research is the use of Javanese letters cards and edugame-based Javanese sound cards is expected that active MI / SD students in reading Javanese script will improve and be able to read them well.